2001
DOI: 10.1128/aac.45.2.633-635.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Approved and Investigational Antifungal Agents against 44 Clinical Isolates of Basidiomycetous Fungi

Abstract: The in vitro activity of amphotericin B, fluconazole, flucytosine, itraconazole, voriconazole, and posaconazole was evaluated against 44 clinical isolates of filamentous basidiomycetous fungi. No statistically significant differences were noted between Schizophyllum commune (n ‫؍‬ 5), Coprinus species (n ‫؍‬ 8), Bjerkandera adusta (n ‫؍‬ 14), and sterile, uncharacterized basidiomycetes (n ‫؍‬ 17).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 14 publications
7
35
0
Order By: Relevance
“…The clinical diagnoses such as invasive mycoses and colonization observed in our study were similar to the respiratory cases reported by Gonzalez et al (36), who identified basidiomycetous fungi through phenotypic methods, with a large number of rare species remaining unidentified. In routine laboratories, the induction of sporulation for definitive identification usually requires about 3 weeks and is associated with high failure rates.…”
Section: Discussionsupporting
confidence: 75%
“…The clinical diagnoses such as invasive mycoses and colonization observed in our study were similar to the respiratory cases reported by Gonzalez et al (36), who identified basidiomycetous fungi through phenotypic methods, with a large number of rare species remaining unidentified. In routine laboratories, the induction of sporulation for definitive identification usually requires about 3 weeks and is associated with high failure rates.…”
Section: Discussionsupporting
confidence: 75%
“…Denning et al reported that the results of a randomized controlled trial (FAST study) that showed a significant quality of life benefit, a fall in IgE, and a modest improvement in rhinitis and morning PEF, but not FEV1, after oral antifungal therapy in patients with severe asthma sensitized to one of several common fungi [23]. Gonzalez GM et al reported that S. commune was susceptible in vitro to ITCZ, amphotericin B, and voriconazole, with MIC values of 0.06, 0.5, and 0.5 µg/ml, respectively [24].…”
Section: Schizophyllum Asthma(結果まちです)mentioning
confidence: 99%
“…González et al (16), reporting in vitro antifungal susceptibility data for 44 clinical isolates of basidiomycetous fungi, indicated that, in addition to Schizophyllum commune and Coprinopsis cinerea, many arthroconidium-forming molds resembling Bjerkandera adusta were being recovered. Many more isolates, however, remained sterile and failed to produce clamp connections and/or lacked spicules suggestive of Schizophyllum commune and were reported as unidentified basidiomycetes (16).…”
Section: Few Filamentous Basidiomycetes Have Been Authenticated As Humentioning
confidence: 99%
“…González et al (16), reporting in vitro antifungal susceptibility data for 44 clinical isolates of basidiomycetous fungi, indicated that, in addition to Schizophyllum commune and Coprinopsis cinerea, many arthroconidium-forming molds resembling Bjerkandera adusta were being recovered. Many more isolates, however, remained sterile and failed to produce clamp connections and/or lacked spicules suggestive of Schizophyllum commune and were reported as unidentified basidiomycetes (16). The characteristics that facilitate recognition of a basidiomycete include rapid growth; colonies that are usually white, cream, or yellow-orange pigmented; the presence of clamp connections and/or crystals; the formation of spicules along the hyphae; and mushroom-or basidiocarp-type fruiting bodies (50).…”
Section: Few Filamentous Basidiomycetes Have Been Authenticated As Humentioning
confidence: 99%
See 1 more Smart Citation